Biological Sex Minimally Affects the Free-Weight Back Squat Load-Velocity Profile When Accounting for Relative Strength: An Exploratory Study - Amdi, CH; Cleather, DJ; Tallent, J (SAGE Publications, 2025)
Research suggests that biological sex and strength level influence the load-velocity profile. However, existing research have not appropriately statistically accounted for the interdependencies between sex and relative strength. This exploratory study investigated load-velocity profiles of 24 resistance-trained participants (14 males, 10 females; back squat 1.69 × and 1.28 × body mass, respectively) using mixed-effects modelling to account for relative strength and individual variability. Participants completed 2–3 incremental back squat loading tests (20 kg to one-repetition maximum [1RM]). 1RM assessments showed excellent reliability, while mean concentric velocity (MCV) at 0–40% of 1RM demonstrated good-to-excellent reliability, with reliability systematically declining at higher relative loads. Small effects of biological sex on load-velocity profiles was found at 0–40% of 1RM (0.07–0.13 m/s, BF = 10.702–47.682, pd = 91–98%), while the effects of relative strength were more pronounced at 0–70% of 1RM (0.18–0.44 m/s, BF = 26.972–2399.000, pd = 96–100%), both with diminishing differences as relative load increased. These findings challenge assumptions about sex as a major load-velocity profile moderator when accounting for relative strength and individual variability. While exploratory and requiring replication, the study recommends future research employ more nuanced statistical methods, recruit homogeneously trained samples, and minimise measurement noise to avoid potential type-I errors.
Keywords: 42 Health Sciences; 4207 Sports Science and Exercise; 11 Medical and Health Sciences; 17 Psychology and Cognitive Sciences; 32 Biomedical and clinical sciences; 42 Health sciences; 52 Psychology; Body composition; gender; resistance training; smartphone-based wearable device